Feasibility Analysis of Old Building Structures Manado State Polytechnic Campus - Julius E. Tenda; Denny B. Pinasang; Mycle Wala; Merci F. Hosang (Jurnal Multidisiplin Madani, 2024)
This study analyzes the old building on the Manado State Polytechnic campus. The aim is to determine the level of feasibility of the old structure of the Manado State Polytechnic campus building. With the establishment of the Manado State Polytechnic campus building since 1987 and the age of the building is around 36 years, therefore it is necessary to re-examine the building to find out whether there are any structural changes or not. The assessment of the feasibility of the old building on the Manado State Polytechnic campus is to evaluate the condition of the materials used, both concrete materials and iron reinforcement materials and the structural system used, also to assess the level of safety and suitability of the materials and structures in each component of the existing structure to the standard load that will be applied in accordance with applicable regulations. The testing method used in evaluating this structure includes visual observation and data collection used during planning and data during implementation. Material testing is carried out using Hammer test and Core Drill to determine the strength of the concrete characteristics which are the basis for analyzing the safety of the building structure